Impact of femoroacetabular impingement and dysplasia of the hip on hip joint sphericity. Issue 2 (March 2020) - Diaz-Lopez, Reynol A; Alonso-Rasgado, M Teresa; Jimenez-Cruz, David; Bailey, Colin G; Board, Tim N
Background: This paper presents a parametric investigation into the effect of femoroacetabular impingement (FAI) and developmental dysplasia of the hip (DDH) on the sphericity of the femoral supra-equatorial region and acetabulum. Methods: Radiographic parameters from x-rays, sphericity calculations and visualisation and joint contact area and pressure from FE models of 10 DDH, FAI and normal hips were analysed and compared both within and between hip groups. Results: The sphericity of the acetabulum and femoral head of both the DDH and FAI groups was found to be less than that for normal hips but the variation in sphericity was greater (range 2.4% for normal hips, compared to 3.3% and 3.1% for the FAI and DDH groups respectively). For the DDH group, femoral head sphericity was found to correlate strongly with 2 of the radiographic parameters used to diagnose the condition, CE angle and Sharp angle. For FAI and DDH hips peak contact pressure primarily occurred in Ilizaliturri Zone 2 (anterior-superior region) in the acetabulum and femoral head which corresponded with increased aspherity in this region compared to the normal hip group. These findings correlate with loading and damage patterns reported in the literature. Additionally, our analysis identified a protrusion of bone in Ilizaliturri Zones 1 and 6 (anterior-inferior region) of the acetabulum of a subgroup of FAI hips, whose existence was confirmed using a full-scale hip model fabricated using a 3D printer, which we believe could result in cartilage damage. Conclusion: We postulate that such protrusions could potentially explain residual symptoms and unaddressed structural deformity in patients who have undergone FAI surgery.